دراسة مقارنة إلمتزاز صبغتين مختلفتين )كاتيونية وأنيونية( على مواد نباتية - صفاء, نصيرة; هنية, نصرات (My University, 2022)
يرتكز عملنا أساسا على دراسة مقارنة إلمتزاز صبغتين مختلفتين، أنيونية )الميثيل البرتقالي )MO ))وكاتيونية )البلورة البنفسجية )CV ))على مسحوق جذوع نخيل التمر )PT .)أظهرت التحاليل الطيفية و المورفولوجية (SEM, XRD, FTIR (أن لهذه المادة الخام تركيبة عضوية غير منتظمة في بنيتها البلورية الضعيفة، و تمتلك سطح مسام ي و غير متجانس. كما أنها تحتوي ًّا ما يجعل إمكانية استخدامها في عملية على العديد من المجموعات الوظيفية القوية كهروستاتيكي اإلمتزاز ممكنة جدا. تناول هذا العمل في مرحلة أولى تجربة إلمكانية إمتزاز الصبغتين على مسحوق PT ثم بعد ذلك يشمل دراسة تأثير بعض العوامل المؤثرة على عملية اإلمتزاز. حيث أظهرت النتائج أن نسبة اإلمتزاز مهمة جد ا )%4.90 )في حالة الـ CV و مقبولة نوعا ما )%41.57 )من أجل الـ MO . الكتل المثلى لمسحوق PT الالزمة إلمتزاز الصبغتين هي 1g و 3g من أجل الـ CV و الـ MO على الترتيب. الكمية الممتزة )Qads )لكال الصبغتين و من أجل كل التراكيز اإلبتدائية المدروسة )l/mg 150−25=C0 )تكون مهمة منذ بداية زمن التالمس ثم تزيد قلـيـال لـتـثـبت فـي لحظـة اإلتـزان )min 45 ≈ te .)عملية اإلمتزاز على الـ PT ز بقو َ ُحفـ تـ ة في الوسط الحمضي بالنسبة لصبغة MO في حين أنها ال تتأثر كثيرا بتغير الـ pH في حالة الـ CV .الزيادة في درجة الحرارة من 20 إلى C°55 تزيد قليال في إمتزاز صبغة CV في حين أنها تؤثر سلبا على فعالية إمتزاز صبغة الـ MO. R2 من خالل قيم تُـظهر الدراسة الحركية أن نموذج الرتبة شبه الثانية ثم نموذج إلوفيتش مالئمان جدا لتفسير حركية إمتزاز الصبغتين. نمذجة اإلمتزاز أثبتت أن إيزوتارم إمتزاز الصبغتين يتبع R2 نموذج فروندليتش وذلك لتسجيله أعلى قيم لـ مقارنة بالنماذج األخرى ، حيث كانت قيمه 9815.0 و 9035.0 من أجل MO و CV على الترتيب. من نتائج الدراسة الترموديناميكية يُالحظ أن قيم °G ∆موجبة في كل درجات الحرارة المدروسة و من أجل كال الصبغتين ، فهذاOur work is based on studying the comparative of two different dyes, anionic (Methyl Orange (MO)) and cationic (Crystal Violet (CV)) on date Palm trunks powder. The morphologic and spectroscopic analysis (FTIR, XRD, SEM) shows that this raw material has an unorganized combination in its crystal structure and it has an heterogeneous and porous surface. Also it contains many strong electrostatic functional groups which make that this matter it very efficient in the adsorption process. The first part of this work contains an experiment of possibility adsorption of two dyes on PT powder. After that, this work it contains a study of influence of the some factors on the adsorption operation. Where the results show the percentage of adsorption is very important (90.4%) in CV case and accepted (57.41%) for MO respectively. The optimal mass of PT powder that’s necessary for the dyes adsorption is 1g and 3g for the CV and the MO respectively. The adsorbed quantity (Qads ) for two dyes and for all initial concentrations (C0=25−150 mg/l) is important from the beginning of the contact time. Then it stabilized at the equilibrium moment (te ≈ 45min) until the end of the experiment. The adsorption operation is very favored in acidic medium for the MO dye while it doesn’t get affected that much with the pH in CV case. The temperature increase from 20C° to 55C° increases slightly the adsorption of CV dye. However, it has a negative effect on the adsorption of MO dye. From the value of R2 , the kinetic study shows that the second-order model and Elovich kinetic model are very suitable for explaining the dyes adsorption process. The modeling of adsorption isotherm proved that the adsorption of the dyes follows the Freundlich model because this is due to the value of R 2 , where it was 0.9815 for MO and 0.9035 for CV. From the results of the thermodynamics study we note that the values of ∆G° are positive for all studied temperatures. It means that the adsorption is spontaneous and unfavorable in this range of studied temperatures. يدل على أن اإلمتزاز في الحالتين غير تلقائي و غير مفضل في هذا المجال الحراري.
مذكرة ماستر كيمياء
Keywords: اإلمتزاز ، الميثيل البرتقالي ، البلورة البنفسجية ، جذوع نخيل التمر ، المواد اللجنوسيلولوزية.; Adsorption, Methyl Orange, Crystal Violet, Date Palm Trunks, Lignocellulosic Material.